Ocean circulation - Colling, Angela (Butterworth Heinemann, in association with the Open University, 2001)
This second edition retains the general structure of the first edition, but. has been updated in the light of recent oceanographic research, and improved. as a teaching text on the basis of feedback from past students and other. readers. Notable additions include new sections addressing the topic of. numerical modelling, and more discussion of natural oscillations in the. ocean-atmosphere system (previously confined to the El Nino phenomenon). In. particular, the Chapter on the North Atlantic now includes a discussion of. the North Atlantic Oscillation, as well as of the Great Salinity Anomaly.